A thick electrode, its fabrication method and application
By adopting alternately arranged first and second active stripe structures in the thick electrodes, the problems of rate performance and cycle life of thick electrodes in the prior art when increasing the electrode thickness are solved, and high energy density, high power and The effect of long cycle life.
Patent Information
- Application Number
- CN202211073068.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-09-02
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2042-09-02
AI Technical Summary
When the existing thick electrode technology increases the electrode thickness, there are problems such as lowering the electrode peeling force, slowing the electrolyte infiltration rate, and increasing internal resistance, resulting in significant deterioration of the rate performance and cycle life.
The structure of the first active stripe and the second active stripe arranged alternately in sequence and horizontally, the active main material of the first active stripe is small in particle size and low in porosity, and the active main material of the second active stripe is large in particle size and high in porosity. The active layer is formed by roll forming, and the wetting rate and wetting degree of the electrolyte are improved.
It significantly improves the rate performance and energy density of thick electrodes, reduces the internal resistance of the battery, extends the cycle life, simplifies the production process, and reduces costs.
Smart Images

Figure CN115394952B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of lithium ion batteries and relates to a thick electrode and a manufacturing method and application thereof. Background Art
[0002] At present, with the rapid development and continuous expansion of new energy vehicles, the market demand for high-energy and high-power power batteries is also increasing. In order to improve the energy density of power batteries, various new materials and technologies are constantly emerging. The main strategies for improving the energy density of power batteries are: ① Develop high-capacity positive and negative electrode materials, such as high-nickel materials and lithium-rich positive electrodes, silicon negative electrodes and metal lithium negative electrodes; ② Develop high-voltage positive electrode materials; ③ Develop high-performance electrolytes; ④ Develop high-performance binders; ⑤ Develop thick electrodes, etc.
[0003] In terms of battery process technology, the development of thick electrodes is the most direct way to improve battery energy density, but there are some problems that need to be solved in thick electrode technology. For example, as the thickness of the electrode increases, although the proportion of inactive materials will be significantly reduced, the peeling force of the electrode will also decrease, the electrolyte infiltration rate will slow down, and the internal resistance of the battery will increase, which will eventually lead to a significant deterioration in the rate performance and cycle life of the battery. A large number of studies have shown that the liquid phase transport of the electrolyte is the rate-controlling step in the electrochemical reaction of thick electrodes, and the liquid phase transport of the electrolyte is closely related to the pore structure and porosity in the electrode. Optimization based on this point can improve the rate performance of thick electrodes.
[0004] For example, CN102655229B uses a pore-forming agent solvent to coat the surface of the electrode. During baking, the solvent evaporates, and the pore-forming agent penetrates into the membrane and recrystallizes to occupy a certain position. Then, the pore-forming agent is baked at a temperature higher than the sublimation or decomposition temperature of the pore-forming agent to form pores, so that the membrane leaves pores and obtains a high-porosity thick electrode. Juliette Billaud et al. (Nature Energy, 2016, 1 (8), 1-6.) use magnetic materials to modify the graphite negative electrode, and use an external magnetic field to control the orientation of graphite particles during the homogenization stage to obtain a low-tortuosity graphite thick electrode. The battery performance is improved only by changing the internal structure of the electrode, so that the lithium storage capacity of the electrode at the actual charging rate is increased by 1.6 to 3 times. Junsu Park (Journal of Industrial and Engineering Chemistry, 2019, 70: 178-185) uses laser groove etching to obtain an array groove thick electrode, thereby significantly improving the battery kinetic performance. However, the above thick electrode manufacturing methods have the following problems:
[0005] 1) When using a pore-forming agent to form pores, the thermal decomposition temperature of the pore-forming agent is incompatible with the electrode baking temperature. The thermal decomposition of the pore-forming agent is easy to form harmful gases, and the pore-forming efficiency is low;
[0006] 2) It is difficult to maintain the oriented structure in the subsequent rolling process by applying a physical field to control the particle orientation, which has poor compatibility with the current roll-to-roll process and high material modification cost;
[0007] 3) Laser pore making is highly destructive to the coating, and is prone to forming molten beads, dust and other substances, resulting in high self-discharge of the battery. In addition, the surface capacity of thick electrodes is significantly reduced, and the energy density is significantly reduced.
[0008] It can be seen that there is currently a lack of a new technology solution that is simpler, more feasible and more compatible with electrode technology, which can adjust the pore structure and porosity in the thick electrode to optimize the liquid phase transport of the electrolyte, thereby obtaining a thick electrode with high energy, high power and long cycle life that meets market demand. Summary of the invention
[0009] In view of the problems existing in the prior art, the purpose of the present invention is to provide a thick electrode and its manufacturing method and application, wherein the active layer of the thick electrode includes a first active stripe and a second active stripe arranged alternately horizontally in sequence; the particle size of the active main material in the first active stripe is small, but the thickness of the first active stripe is the same as that of the second active stripe, so that the porosity of the first active stripe is lower than that of the second active stripe, and the width of the first active stripe is maintained at 5 to 20 times the width of the second active stripe. The first active stripe of the present invention is relatively wide, which ensures the high capacity and high power of the thick electrode. On this basis, the particle size of the active main material in the second active stripe is relatively large, and after roll forming, the porosity is relatively large, and it is distributed in the gap formed by the first active stripe with a narrow width, which can significantly improve the infiltration rate and degree of the electrolyte with the entire active layer, and at the same time can reduce the internal resistance of the battery, thereby improving the rate performance of the thick electrode.
[0010] To achieve this object, the present invention adopts the following technical solutions:
[0011] In the first aspect, the present invention provides a thick electrode, which includes a current collector and an active layer located on the current collector, the active layer including a first active stripe and a second active stripe arranged horizontally alternately in sequence; the first active stripe includes an active main material, a conductive agent and a binder, and the component material of the second active stripe is the same as that of the first active stripe; the particle size of the active main material in the first active stripe is smaller than the particle size of the active main material in the second active stripe; the thickness of the first active stripe is the same as the thickness of the second active stripe; the porosity of the first active stripe is lower than the porosity of the second active stripe; the width of the first active stripe is 5 to 20 times the width of the second active stripe.
[0012] The present invention sets a striped active layer and controls the first active stripe to have a larger width to ensure the high capacity and high power of the thick electrode. On this basis, the particle size of the active main material in the second active stripe is larger. After roller forming, the porosity is larger and distributed in the gap formed by the first active stripe with a narrower width, which mainly plays the role of a fast channel, can significantly improve the infiltration rate and infiltration degree of the electrolyte with the entire active layer, and at the same time can reduce the internal resistance of the battery, thereby improving the rate performance of the thick electrode.
[0013] In the electrode, as the thickness of the electrode increases, the main factor limiting its rate performance is the liquid phase transmission process of the electrolyte, because the size of the active main material particles will have a significant impact on the electrode pore structure, and therefore will also affect the process of liquid phase transmission; the larger the active main material particles, the larger the pores that can be formed between the particles, which is conducive to the transmission of the electrolyte in the thickness direction of the electrode, but the active main material particles are too large, resulting in a too small compaction density of the thick electrode, which is not conducive to the improvement of energy density. In addition, the active main material particles are too large, which will also significantly reduce its solid phase diffusion coefficient, resulting in a significant increase in concentration polarization. In the thick electrode described in the present invention, the large pores formed by the large particle active main material coated by the array are conducive to the rapid infiltration and diffusion of the electrolyte inside the thick electrode, thereby significantly improving the kinetic performance of the thick electrode. However, the second active stripe area formed by the large particles should not be too large, otherwise, on the one hand, it is easy to cause a significant decrease in the compaction density of the thick electrode and a serious attenuation of the battery energy density. On the other hand, large particles are not conducive to the diffusion of solid-phase lithium ions, and the wider second active stripe area of large particles causes a significant attenuation of the thick electrode rate performance.
[0014] The following are preferred technical solutions of the present invention, but are not intended to be limitations of the technical solutions provided by the present invention. Through the following technical solutions, the technical objectives and beneficial effects of the present invention can be better achieved and realized.
[0015] As a preferred technical solution of the present invention, the width of the first active stripe is 0.5 to 50 mm, for example, 0.5 mm, 1 mm, 5 mm, 10 mm, 15 mm, 20 mm, 25 mm, 30 mm, 35 mm, 40 mm, 45 mm or 50 mm, but is not limited to the listed values, and other unlisted values within the above numerical range are also applicable.
[0016] Preferably, the porosity of the first active stripe is 20-50%, for example 20%, 25%, 30%, 35%, 40%, 45% or 50%, etc., but is not limited to the listed values, and other unlisted values within the above numerical range are also applicable.
[0017] Preferably, the active layer is disposed on the surface of one side or both sides of the current collector.
[0018] As a preferred technical solution of the present invention, the thickness of the first active stripes and the second active stripes are both 150 to 350 μm, for example, 150 μm, 180 μm, 210 μm, 240 μm, 270 μm, 300 μm, 330 μm or 350 μm, but are not limited to the listed values, and other unlisted values within the above numerical range are also applicable.
[0019] As a preferred technical solution of the present invention, the particle size of the active main material in the first active stripe is 20 to 80% of the particle size of the active main material in the second active stripe, for example, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75% or 80%, etc., but is not limited to the listed values, and other unlisted values within the above numerical range are equally applicable.
[0020] Preferably, the active main material includes a positive electrode main material or a negative electrode main material.
[0021] Preferably, the positive electrode main material includes any one of lithium cobalt oxide, lithium manganese oxide, lithium nickel oxide, nickel cobalt manganese oxide or nickel cobalt aluminum oxide, or a combination of at least two of them. Typical but non-limiting examples of the combination include a combination of lithium cobalt oxide and lithium manganese oxide, a combination of lithium cobalt oxide and lithium nickel oxide, a combination of lithium manganese oxide and lithium nickel oxide, and a combination of lithium manganese oxide and lithium nickel cobalt aluminum oxide.
[0022] Preferably, the negative electrode main material includes any one or a combination of at least two of graphite, hard carbon, soft carbon, silicon, silicon carbon or tin. Typical but non-limiting examples of the combination include a combination of graphite and soft carbon, a combination of graphite and hard carbon, a combination of graphite and tin, a combination of hard carbon and tin, a combination of soft carbon and tin, a combination of silicon and tin, and a combination of silicon carbon and tin.
[0023] As a preferred technical solution of the present invention, the conductive agent includes any one of carbon black, carbon fiber, carbon nanotube or graphene, or a combination of at least two of them. Typical but non-limiting examples of the combination include a combination of carbon black and carbon fiber, a combination of carbon black and carbon nanotube, a combination of carbon black and graphene, a combination of carbon fiber and carbon nanotube, a combination of carbon fiber and graphene, and a combination of carbon nanotube and graphene.
[0024] As a preferred technical solution of the present invention, the binder content in the first active stripes is lower than the binder content in the second active stripes.
[0025] Preferably, the binder comprises any one of sodium hydroxymethyl cellulose, styrene-butadiene rubber, polyvinylidene fluoride or polyacrylic acid, or a combination of at least two thereof. Typical but non-limiting examples of the combination include a combination of sodium hydroxymethyl cellulose and styrene-butadiene rubber, a combination of sodium hydroxymethyl cellulose and polyvinylidene fluoride, a combination of sodium hydroxymethyl cellulose and polyacrylic acid, a combination of styrene-butadiene rubber and polyvinylidene fluoride, a combination of styrene-butadiene rubber and polyacrylic acid, and a combination of polyvinylidene fluoride and polyacrylic acid.
[0026] In a second aspect, the present invention provides a method for manufacturing the thick electrode according to the first aspect, the manufacturing method comprising the following steps:
[0027] (1) Selecting active main materials, conductive agents and binders of the same material to prepare first slurry and second slurry respectively; the particle size of the active main material in the first slurry is smaller than the particle size of the active main material in the second slurry;
[0028] (2) coating the first slurry in step (1) on the current collector to form first slurry stripes with gaps; the width of the first slurry stripes is 5 to 20 times the width of the gaps;
[0029] (3) coating the second slurry obtained in step (1) in the gap obtained in step (2) to form second slurry stripes;
[0030] (4) Baking and rolling are performed in sequence to make the first slurry stripes form first active stripes and the second slurry stripes form second active stripes, and the thickness of the first active stripes is controlled to be equal to the thickness of the second slurry stripes, so that the porosity of the first active stripes is lower than that of the second active stripes, and the first active stripes and the second active stripes are alternately arranged in sequence to form an active layer to obtain a thick electrode.
[0031] It should be noted that the widths of the first active stripes and the second active stripes formed by the first slurry stripes and the second slurry stripes respectively after rolling remain unchanged, that is, the actual width direction does not extend, so the final width is the same as the width during coating.
[0032] As a preferred technical solution of the present invention, the content of the binder in the first slurry is 30 to 90% of the content of the binder in the second slurry, for example, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85% or 90%, etc., but is not limited to the listed values, and other unlisted values within the above numerical range are also applicable.
[0033] The present invention preferably makes the binder content in the second slurry higher, which is beneficial for the diffusion of the binder from the second slurry stripes to the first slurry stripes during baking and rolling, significantly improving the binder migration, improving the uniformity of the binder distribution in the thick electrode, and improving the peel strength.
[0034] Preferably, based on the total mass of the active main material, conductive agent and binder in the first slurry as 100wt%, the content of the binder is 1-3wt%, for example, 1%, 1.2%, 1.4%, 1.6%, 1.8%, 2%, 2.2%, 2.4%, 2.6%, 2.8% or 3%, etc., but is not limited to the listed values, and other values not listed within the above numerical range are also applicable.
[0035] Preferably, the thickness of the first slurry stripes and the second slurry stripes are both 200-450μm, for example, 200μm, 225μm, 250μm, 275μm, 300μm, 325μm, 350μm, 375μm, 400μm, 425μm or 450μm, but are not limited to the listed values, and other unlisted values within the above numerical range are also applicable.
[0036] As a preferred technical solution of the present invention, the production method comprises the following steps:
[0037] (1) Selecting active main materials, conductive agents, binders and solvents of the same material, stirring and dispersing them, respectively, to prepare a first slurry and a second slurry; controlling the particle size of the active main material in the first slurry to be 20-80% of the particle size of the active main material in the second slurry; the active main material comprises a positive electrode main material or a negative electrode main material; the positive electrode main material comprises any one of lithium cobalt oxide, lithium manganese oxide, lithium nickel oxide, lithium nickel cobalt manganese oxide or lithium nickel cobalt aluminum oxide, or a combination of at least two thereof; the negative electrode main material comprises any one of graphite, hard carbon, soft carbon, silicon, silicon carbon or tin, or a combination of at least two thereof;
[0038] Taking the total mass of the active main material, the conductive agent and the binder in the first slurry as 100wt%, the content of the binder is 1-3wt%; the content of the binder in the first slurry is controlled to be 30-90% of the content of the binder in the second slurry; the binder includes any one of sodium hydroxymethyl cellulose, styrene-butadiene rubber, polyvinylidene fluoride or polyacrylic acid or a combination of at least two; the conductive agent includes any one of carbon black, carbon fiber, carbon nanotube or graphene or a combination of at least two;
[0039] (2) coating the first slurry in step (1) on the current collector to form first slurry stripes with gaps; the gaps are 0.5 to 50 mm, the width of the first slurry stripes is 5 to 20 times the gaps; the thickness of the first slurry stripes is 200 to 450 μm;
[0040] (3) coating the second slurry obtained in step (1) in the gap obtained in step (2) to form second slurry stripes having the same thickness as the first slurry stripes;
[0041] (4) Baking and rolling are performed in sequence to make the first slurry stripes form first active stripes and the second slurry stripes form second active stripes, which are arranged alternately in sequence to form an active layer; the thickness of the first active stripes is equal to that of the second active stripes, both of which are 150 to 350 μm, and the porosity of the first active stripes is controlled to be 20 to 50%, and the porosity of the second active stripes is higher than that of the first active stripes, so as to obtain a thick electrode.
[0042] In a third aspect, the present invention provides an application of the thick electrode described in the first aspect or the thick electrode obtained by the manufacturing method described in the second aspect, wherein the application includes using the thick electrode in a lithium-ion battery.
[0043] Compared with the prior art solutions, the present invention has at least the following beneficial effects:
[0044] (1) In the present invention, the active material in the first active stripes has a small particle size and a small porosity, and the first active stripes have a large width, which can ensure the capacity and power of the thick electrode. On this basis, the second active stripes containing the large particle size active main material have a high porosity and a large pore size after rolling, and are distributed in the gaps of the first active stripes. They are alternately arranged with the first active stripes to form a striped active layer, which can significantly improve the infiltration rate and wettability of the electrolyte in the entire active layer, effectively reduce the internal resistance of the battery, and improve the rate performance;
[0045] (2) Compared with the prior art of forming holes in thick electrodes, the presence of the second active stripes in the present invention can significantly improve the energy density of the thick electrode. In addition, it can effectively alleviate the undesirable problems such as wrinkling of the electrode during coating and rolling of the thick electrode. Compared with the manufacturing process of the thick electrode with holes, the manufacturing method of the present invention has a simple process, high production efficiency, and significantly reduces the manufacturing cost of the thick electrode.
[0046] (3) The binder content in the second slurry of the present invention is higher than the binder content in the first slurry. Therefore, during coating and baking, the binder in the second slurry stripes can radiate and diffuse into the first slurry stripes, significantly improving the binder migration condition, improving the uniformity of the binder distribution of the entire thick electrode, and effectively improving the peel strength. BRIEF DESCRIPTION OF THE DRAWINGS
[0047] Figure 1 is a schematic top view of the lithium iron phosphate thick electrode obtained in Example 1 of the present invention;
[0048] Figure 2 yes Figure 1 Schematic diagram of the cross section in the AA direction;
[0049] In the figure: 1-first active stripe, 2-second active stripe, 3-current collector. DETAILED DESCRIPTION
[0050] The technical solution of the present invention is further described below in conjunction with the accompanying drawings and through specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0051] Example 1
[0052] This embodiment provides a lithium iron phosphate thick electrode, and the manufacturing method of the lithium iron phosphate thick electrode comprises the following steps:
[0053] (1) stirring and dispersing carbon black, PVDF (polyvinylidene fluoride) and lithium iron phosphate with a median particle size D50 of 0.5 μm in NMP (N-methylpyrrolidone), wherein the content of PVDF is 2 wt %, to obtain a uniform first slurry; stirring and dispersing carbon black, PVDF and lithium iron phosphate with a median particle size D50 of 1.2 μm in NMP, wherein the content of PVDF is 3 wt %, to obtain a uniform second slurry;
[0054] (2) coating the first slurry in step (1) on an aluminum current collector to form an array of first slurry stripes with a gap of 2 mm and a width of 20 mm, and the thickness of the first slurry stripes is 300 μm;
[0055] (3) coating the second slurry obtained in step (1) in the gap obtained in step (2) to form second slurry stripes having the same thickness as the first slurry stripes;
[0056] (4) Baking and rolling are performed in sequence to form the first slurry stripes into first active stripes and the second slurry stripes into second active stripes; the thickness of the first active stripes and the second active stripes are equal, both of which are 200 μm, and they are alternately arranged in sequence to form an active layer, thereby obtaining a lithium iron phosphate thick electrode.
[0057] The structural schematic diagram of the lithium iron phosphate thick electrode in this embodiment is as follows Figure 1 and Figure 2As shown, the lithium iron phosphate thick electrode includes a current collector 3 made of aluminum foil, and an active layer formed by first active stripes 1 and second active stripes 2 located on the current collector 3 being horizontally alternately arranged in sequence; the width of the first active stripes 1 is 20 mm, the width of the second active stripes 2 is 2 mm, and the thickness of the first active stripes 1 and the second active stripes 2 are both 200 μm.
[0058] Example 2
[0059] This embodiment provides a lithium iron phosphate thick electrode, and the manufacturing method of the lithium iron phosphate thick electrode comprises the following steps:
[0060] (1) stirring and dispersing carbon black, PVDF and lithium iron phosphate with a median particle size D50 of 0.8 μm in NMP, wherein the content of PVDF is 2 wt %, to obtain a uniform first slurry; stirring and dispersing carbon black, PVDF and lithium iron phosphate with a median particle size D50 of 1.5 μm in NMP, wherein the content of PVDF is 3 wt %, to obtain a uniform second slurry;
[0061] (2) coating the first slurry in step (1) on an aluminum current collector to form an array of first slurry stripes with a gap of 4 mm and a width of 25 mm, and the thickness of the first slurry stripes is 300 μm;
[0062] (3) coating the second slurry obtained in step (1) in the gap obtained in step (2) to form second slurry stripes having the same thickness as the first slurry stripes;
[0063] (4) Baking and rolling are performed in sequence to form the first slurry stripes into first active stripes and the second slurry stripes into second active stripes; the thickness of the first active stripes and the second active stripes are equal, both of which are 200 μm, and they are alternately arranged in sequence to form an active layer, thereby obtaining a lithium iron phosphate thick electrode.
[0064] Example 3
[0065] This embodiment provides a lithium iron phosphate thick electrode, and the manufacturing method of the lithium iron phosphate thick electrode comprises the following steps:
[0066] (1) stirring and dispersing carbon black, PVDF and lithium iron phosphate with a median particle size D50 of 0.8 μm in NMP, wherein the content of PVDF is 2 wt %, to obtain a uniform first slurry; stirring and dispersing carbon black, PVDF and lithium iron phosphate with a median particle size D50 of 1.5 μm in NMP, wherein the content of PVDF is 3 wt %, to obtain a uniform second slurry;
[0067] (2) coating the first slurry in step (1) on an aluminum current collector to form an array of first slurry stripes with a gap of 5 mm and a width of 50 mm, and the thickness of the first slurry stripes is 400 μm;
[0068] (3) coating the second slurry obtained in step (1) in the gap obtained in step (2) to form second slurry stripes having the same thickness as the first slurry stripes;
[0069] (4) Baking and rolling are performed in sequence to form the first slurry stripes into first active stripes and the second slurry stripes into second active stripes; the thickness of the first active stripes and the second active stripes are equal, both of which are 300 μm, and they are alternately arranged in sequence to form an active layer, thereby obtaining a lithium iron phosphate thick electrode.
[0070] Example 4
[0071] This embodiment provides a graphite thick electrode, and the manufacturing method of the graphite thick electrode comprises the following steps:
[0072] (1) carbon black is used as a conductive agent, CMC (sodium carboxymethyl cellulose) and SBR (styrene-butadiene rubber) are used as binders, and graphite with a median particle size D50 of 6 μm is stirred and dispersed in NMP, wherein the content of CMC and SBR is 2.5 wt %, to obtain a uniform first slurry; carbon black is used as a conductive agent, CMC and SBR are used as binders, and graphite with a median particle size D50 of 15 μm is stirred and dispersed in NMP, wherein the content of CMC and SBR is 3.2 wt %, to obtain a uniform second slurry;
[0073] (2) coating the first slurry in step (1) on an aluminum current collector to form an array of first slurry stripes with a gap of 2.5 mm and a width of 20 mm, and the thickness of the first slurry stripes is 200 μm;
[0074] (3) coating the second slurry obtained in step (1) in the gap obtained in step (2) to form second slurry stripes having the same thickness as the first slurry stripes;
[0075] (4) Baking and rolling are performed in sequence to form the first slurry stripes into first active stripes and the second slurry stripes into second active stripes; the thickness of the first active stripes and the second active stripes are equal, both of which are 150 μm, and they are alternately arranged in sequence to form an active layer, thereby obtaining a graphite thick electrode.
[0076] Example 5
[0077] This embodiment provides a graphite thick electrode, and the manufacturing method of the graphite thick electrode comprises the following steps:
[0078] (1) carbon black as a conductive agent, CMC and SBR as binders, and graphite with a median particle size D50 of 2.4 μm are stirred and dispersed in NMP, wherein the content of CMC and SBR is 1 wt %, to obtain a uniform first slurry; carbon black as a conductive agent, CMC and SBR as binders, and graphite with a median particle size D50 of 12 μm are stirred and dispersed in NMP, wherein the content of CMC and SBR is 3.33 wt %, to obtain a uniform second slurry;
[0079] (2) coating the first slurry in step (1) on an aluminum current collector to form an array of first slurry stripes with a gap of 5 mm and a width of 40 mm, and the thickness of the first slurry stripes is 250 μm;
[0080] (3) coating the second slurry obtained in step (1) in the gap obtained in step (2) to form second slurry stripes having the same thickness as the first slurry stripes;
[0081] (4) Baking and rolling are performed in sequence to form the first slurry stripes into first active stripes and the second slurry stripes into second active stripes; the thickness of the first active stripes and the second active stripes are equal, both of which are 180 μm, and they are alternately arranged in sequence to form an active layer, thereby obtaining a graphite thick electrode.
[0082] Example 6
[0083] This embodiment provides a graphite thick electrode, and the manufacturing method of the graphite thick electrode comprises the following steps:
[0084] (1) carbon black as a conductive agent, CMC and SBR as binders, and graphite with a median particle size D50 of 4 μm are stirred and dispersed in NMP, wherein the content of CMC and SBR is 3 wt %, to obtain a uniform first slurry; carbon black as a conductive agent, CMC and SBR as binders, and graphite with a median particle size D50 of 10 μm are stirred and dispersed in NMP, wherein the content of CMC and SBR is 3.33 wt %, to obtain a uniform second slurry;
[0085] (2) coating the first slurry in step (1) on an aluminum current collector to form an array of first slurry stripes with a gap of 6 mm and a width of 50 mm, and the thickness of the first slurry stripes is 450 μm;
[0086] (3) coating the second slurry obtained in step (1) in the gap obtained in step (2) to form second slurry stripes having the same thickness as the first slurry stripes;
[0087] (4) Baking and rolling are performed in sequence to form the first slurry stripes into first active stripes and the second slurry stripes into second active stripes; the thickness of the first active stripes and the second active stripes are equal, both of which are 350 μm, and they are alternately arranged in sequence to form an active layer, thereby obtaining a graphite thick electrode.
[0088] Example 7
[0089] The present embodiment provides a lithium iron phosphate thick electrode. In the method for manufacturing the lithium iron phosphate thick electrode, except that in step (1), carbon black, PVDF and lithium iron phosphate with a median particle size D50 of 10 μm are stirred and dispersed in NMP, wherein the PVDF content is 3 wt % to obtain a uniform second slurry, other conditions are exactly the same as those in Example 1.
[0090] Example 8
[0091] The present embodiment provides a lithium iron phosphate thick electrode. In the method for manufacturing the lithium iron phosphate thick electrode, except that in step (1), carbon black, PVDF and lithium iron phosphate with a median particle size D50 of 5 μm are stirred and dispersed in NMP, wherein the PVDF content is 3wt%, to obtain a uniform second slurry, other conditions are exactly the same as those in Example 1.
[0092] Example 9
[0093] The present embodiment provides a lithium iron phosphate thick electrode. In the method for manufacturing the lithium iron phosphate thick electrode, except that in step (1), carbon black, PVDF and lithium iron phosphate with a median particle size D50 of 0.625 μm are stirred and dispersed in NMP, wherein the PVDF content is 3 wt% to obtain a uniform second slurry, other conditions are exactly the same as those in Example 1.
[0094] Example 10
[0095] The present embodiment provides a lithium iron phosphate thick electrode. In the method for manufacturing the lithium iron phosphate thick electrode, except that in step (1), carbon black, PVDF and lithium iron phosphate with a median particle size D50 of 0.56 μm are stirred and dispersed in NMP, wherein the PVDF content is 3 wt % to obtain a uniform second slurry, other conditions are exactly the same as those in Example 1.
[0096] Embodiment 11
[0097] The present embodiment provides a lithium iron phosphate thick electrode. In the method for manufacturing the lithium iron phosphate thick electrode, except that in step (1), carbon black, PVDF and lithium iron phosphate with a median particle size D50 of 10 μm are stirred and dispersed in NMP, wherein the PVDF content is 8 wt % to obtain a uniform second slurry, other conditions are exactly the same as those in Example 1.
[0098] Example 12
[0099] The present embodiment provides a lithium iron phosphate thick electrode. In the method for manufacturing the lithium iron phosphate thick electrode, except that in step (1), carbon black, PVDF and lithium iron phosphate with a median particle size D50 of 10 μm are stirred and dispersed in NMP, wherein the PVDF content is 6.6 wt% to obtain a uniform second slurry, other conditions are exactly the same as those in Example 1.
[0100] Example 13
[0101] The present embodiment provides a lithium iron phosphate thick electrode. In the method for manufacturing the lithium iron phosphate thick electrode, except that in step (1), carbon black, PVDF and lithium iron phosphate with a median particle size D50 of 10 μm are stirred and dispersed in NMP, wherein the PVDF content is 2.23 wt% to obtain a uniform second slurry, other conditions are exactly the same as those in Example 1.
[0102] Embodiment 14
[0103] The present embodiment provides a lithium iron phosphate thick electrode. In the method for manufacturing the lithium iron phosphate thick electrode, except that in step (1), carbon black, PVDF and lithium iron phosphate with a median particle size D50 of 10 μm are stirred and dispersed in NMP, wherein the PVDF content is 2 wt % to obtain a uniform second slurry, other conditions are exactly the same as those in Example 1.
[0104] Embodiment 15
[0105] The present embodiment provides a lithium iron phosphate thick electrode. In the method for manufacturing the lithium iron phosphate thick electrode, except that in step (2), the first slurry is coated on the aluminum current collector to form an array formed by first slurry stripes with a gap of 4 mm and a width of 20 mm, other conditions are exactly the same as those in Example 1.
[0106] Example 16
[0107] The present embodiment provides a lithium iron phosphate thick electrode. In the method for manufacturing the lithium iron phosphate thick electrode, except that in step (2), the first slurry is coated on the aluminum current collector to form an array formed by first slurry stripes with a gap of 1 mm and a width of 20 mm, other conditions are exactly the same as those in Example 1.
[0108] Comparative Example 1
[0109] This comparative example provides a lithium iron phosphate thick electrode, and the manufacturing method of the lithium iron phosphate thick electrode comprises the following steps:
[0110] Carbon black, PVDF and lithium iron phosphate with a median particle size D50 of 0.5 μm are stirred and dispersed in NMP, wherein the PVDF content is 2wt%, to obtain a uniform slurry; the slurry is coated on an aluminum current collector to form a slurry layer with a thickness of 300 μm; baking and rolling are performed in sequence to form an active layer with a thickness of 200 μm, thereby obtaining the lithium iron phosphate thick electrode.
[0111] Comparative Example 2
[0112] This comparative example provides a lithium iron phosphate thick electrode, and the manufacturing method of the lithium iron phosphate thick electrode comprises the following steps:
[0113] Carbon black, PVDF and lithium iron phosphate with a median particle size D50 of 0.8 μm are stirred and dispersed in NMP, wherein the PVDF content is 2wt%, to obtain a uniform slurry; the slurry is coated on an aluminum current collector to form a slurry layer with a thickness of 300 μm; baking and rolling are performed in sequence to form an active layer with a thickness of 200 μm, thereby obtaining a lithium iron phosphate thick electrode.
[0114] Comparative Example 3
[0115] This comparative example provides a lithium iron phosphate thick electrode, and the manufacturing method of the lithium iron phosphate thick electrode comprises the following steps:
[0116] Carbon black, PVDF and lithium iron phosphate with a median particle size D50 of 0.8 μm are stirred and dispersed in NMP, wherein the PVDF content is 2wt%, to obtain a uniform slurry; the slurry is coated on an aluminum current collector to form a slurry layer with a thickness of 400 μm; baking and rolling are performed in sequence to form an active layer with a thickness of 300 μm, thereby obtaining a lithium iron phosphate thick electrode.
[0117] Comparative Example 4
[0118] This comparative example provides a graphite thick electrode, and the manufacturing method of the graphite thick electrode comprises the following steps:
[0119] Carbon black is used as a conductive agent, CMC and SBR are used as binders, and graphite with a median particle size D50 of 6 μm is stirred and dispersed in NMP, wherein the content of CMC and SBR is 2.5wt%, to obtain a uniform slurry; the slurry is coated on an aluminum current collector to form a slurry layer with a thickness of 200 μm; baking and rolling are performed in sequence to form an active layer with a thickness of 150 μm, thereby obtaining a graphite thick electrode.
[0120] Comparative Example 5
[0121] This comparative example provides a lithium iron phosphate thick electrode. In the method for preparing the lithium iron phosphate thick electrode, except that in step (1), carbon black, PVDF and lithium iron phosphate with a median particle size D50 of 0.5 μm are stirred and dispersed in NMP, wherein the PVDF content is 3 wt% to obtain a uniform second slurry, other conditions are exactly the same as those in Example 1.
[0122] Comparative Example 6
[0123] This comparative example provides a lithium iron phosphate thick electrode. In the method for manufacturing the lithium iron phosphate thick electrode, except that in step (2), the first slurry is coated on the aluminum current collector to form an array formed by first slurry stripes with a gap of 10 mm and a width of 20 mm, other conditions are exactly the same as those in Example 1.
[0124] Comparative Example 7
[0125] This comparative example provides a lithium iron phosphate thick electrode. In the method for manufacturing the lithium iron phosphate thick electrode, except that in step (2), the first slurry is coated on the aluminum current collector to form an array formed by first slurry stripes with a gap of 0.5 mm and a width of 20 mm, other conditions are exactly the same as those in Example 1.
[0126] Comparative Example 8
[0127] This comparative example provides a lithium iron phosphate thick electrode. In the method for manufacturing the lithium iron phosphate thick electrode, except that in step (2), the first slurry is coated on the aluminum current collector to form an array formed by first slurry stripes with a gap of 0.2 mm and a width of 20 mm, other conditions are exactly the same as those in Example 1.
[0128] At 25°C, the capacity retention rates of the batteries prepared in the embodiments and comparative examples were tested at different rates. The voltage range of the battery whose electrode active material is lithium iron phosphate is 2.5-3.65V, the voltage range of lithium cobalt oxide and lithium nickel cobalt manganese oxide is 2.5-4.2V, and the voltage range of graphite is 2.5-3.65V. The rates are 0.5C, 1C, 2C and 3C, respectively. The capacity retention rate is calculated by dividing the capacity of XC by the capacity of 0.33C (X is 0.5, 1, 2 or 3) to obtain the capacity retention rate at the corresponding rate. The results are shown in Table 1.
[0129] Table 1
[0130]
[0131]
[0132] It can be seen from Table 1 that:
[0133] (1) By comparing Example 1 with Comparative Example 1, it is found that the thick electrode preparation method provided by the present invention can significantly improve the thick electrode rate performance compared with the conventional thick electrode preparation method; the second active stripes and the first active stripes composed of large particles distributed in an array can significantly reduce the internal resistance of the thick electrode, thereby improving the battery rate performance;
[0134] (2) Comparing Example 1 with Examples 7-10 and Comparative Example 5, it is found that the median particle size of the active material in the second active stripe has a significant effect on the rate performance of the thick electrode. When the median particle size of the second active coating is too large, the solid phase diffusion path of lithium ions is significantly increased, and the concentration polarization is aggravated. In addition, when the median particle size of the second active particles is too large, the surface binder content increases, and the electrode resistance increases. Therefore, the second active particles that are too large are not conducive to the improvement of the rate performance of the thick electrode. On the contrary, if the median particle size of the second active particles is too small, the pores of the corresponding second active stripes are small, and the infiltration of the electrolyte in the thick electrode cannot be effectively improved. Therefore, the internal resistance of the thick electrode is large and the rate performance is also poor. The particle size of the active main material in the first slurry optimized by the present invention is 20 to 80% of the particle size of the active main material in the second slurry.
[0135] (3) Comparing Example 1 with Examples 11-14, it is found that the higher binder content of the second active stripes than that of the first active stripes can effectively improve the rate performance of the thick electrode. When the binder content of the second active stripes is low, the binder migrates to the electrode surface during the coating and baking of the thick electrode, and the distribution is uneven. At the same time, the low binder content at the interface between the active coating and the current collector leads to a significant decrease in the peeling force, a significant increase in the interface resistance, an increase in the internal resistance of the thick electrode, and a significant attenuation of the rate performance. When the binder content of the second active stripes is too high, on the one hand, the high binder hinders the electrode pores and cannot achieve rapid absorption and infiltration of the electrolyte in the second active stripes. On the other hand, the high binder content leads to a significant increase in the resistivity of the second active stripes, and the internal resistance of the thick electrode is also significantly increased, so that the battery rate performance is significantly attenuated. Therefore, the content of the binder in the first slurry optimized by the present invention is 30 to 90% of the content of the binder in the second slurry.
[0136] (4) By comparing Example 1 with Examples 15-16 and Comparative Examples 6-8, it was found that: if the ratio of the width of the first active stripe to the width of the second active stripe is too large or too small, the rate performance of the thick electrode will be attenuated. If the second active stripe is too small, the electrolyte absorption rate is low. At the same time, the amount of binder in the second active stripe is small, and it is difficult to effectively alleviate the problems of reduced peeling force and increased internal resistance caused by the migration of the binder in the first active stripe. Similarly, if the width of the second active stripe is too high, the effective compaction density of the thick electrode will be significantly reduced. At the same time, too much binder in the second active stripe will also significantly increase the resistivity of the thick electrode, resulting in an increase in the internal resistance of the thick electrode and a significant deterioration in the rate performance. Based on the experimental results, the width of the first active stripe preferably selected in the present invention is 5 to 20 times the width of the second active stripe.
[0137] The present invention illustrates the detailed structural features of the present invention through the above embodiments, but the present invention is not limited to the above detailed structural features, that is, it does not mean that the present invention must rely on the above detailed structural features to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the components selected by the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
[0138] The preferred embodiments of the present invention are described in detail above. However, the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, a variety of simple modifications can be made to the technical solution of the present invention, and these simple modifications all belong to the protection scope of the present invention.
[0139] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.
[0140] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.
Claims
1. A thick electrode, characterized in that: The thick electrode includes a current collector and an active layer located on the current collector, the active layer includes a first active stripe and a second active stripe arranged alternately horizontally in sequence; the first active stripe includes an active main material, a conductive agent and a binder, the active main material includes a positive electrode main material or a negative electrode main material, the component material of the second active stripe is the same as that of the first active stripe, and the binder content in the first active stripe is lower than the binder content in the second active stripe; the particle size of the active main material in the first active stripe is smaller than the particle size of the active main material in the second active stripe; the thickness of the first active stripe is the same as that of the second active stripe and is 200-350 μm; the width of the first active stripe is 5-20 times the width of the second active stripe; the porosity of the second active stripe is higher than that of the first active stripe.
2. The thick electrode according to claim 1, characterized in that The width of the first active stripe is 0.5-50 mm.
3. The thick electrode according to claim 1, characterized in that The porosity of the first active stripes is 20-50%.
4. The thick electrode according to claim 1, characterized in that The active layer is disposed on the surface of one side or both sides of the current collector.
5. The thick electrode according to claim 1, characterized in that The particle size of the active main material in the first active stripes is 20 to 80% of the particle size of the active main material in the second active stripes.
6. The thick electrode according to claim 1, characterized in that The positive electrode main material includes any one of lithium cobalt oxide, lithium manganese oxide, lithium nickel oxide, lithium nickel cobalt manganese oxide or lithium nickel cobalt aluminum oxide, or a combination of at least two thereof.
7. The thick electrode according to claim 1, characterized in that The negative electrode main material includes any one of graphite, hard carbon, soft carbon, silicon, silicon-carbon or tin, or a combination of at least two thereof.
8. The thick electrode according to claim 1, characterized in that The conductive agent includes any one of carbon black, carbon fiber, carbon nanotube or graphene, or a combination of at least two of them.
9. The thick electrode according to claim 1, characterized in that The binder includes any one of sodium hydroxymethyl cellulose, styrene-butadiene rubber, polyvinylidene fluoride or polyacrylic acid, or a combination of at least two of them.
10. A method for manufacturing a thick electrode according to any one of claims 1 to 9, characterized in that: The production method comprises the following steps: (1) Selecting active main materials, conductive agents and binders of the same material to prepare first slurry and second slurry respectively; the particle size of the active main material in the first slurry is smaller than the particle size of the active main material in the second slurry; (2) coating the first slurry in step (1) on the current collector to form first slurry stripes with gaps; the width of the first slurry stripes is 5 to 20 times the width of the gaps; (3) coating the second slurry obtained in step (1) in the gap obtained in step (2) to form second slurry stripes; (4) Baking and rolling are performed in sequence to make the first slurry stripes form first active stripes and the second slurry stripes form second active stripes, and the thickness of the first active stripes is controlled to be equal to the thickness of the second slurry stripes, so that the porosity of the first active stripes is lower than that of the second active stripes, and the first active stripes and the second active stripes are alternately arranged in sequence to form an active layer to obtain a thick electrode.
11. The method for manufacturing a thick electrode according to claim 10, characterized in that: The content of the binder in the first slurry is 30 to 90% of the content of the binder in the second slurry.
12. The method for manufacturing a thick electrode according to claim 10, characterized in that: Based on the total weight of the active main material, the conductive agent and the binder in the first slurry being 100 wt %, the content of the binder is 1 to 3 wt %.
13. The method for manufacturing a thick electrode according to claim 10, characterized in that: The thickness of the first slurry stripes and the second slurry stripes are both 200-450 μm.
14. The method for manufacturing a thick electrode according to claim 10, characterized in that: The production method comprises the following steps: (1) Selecting active main materials, conductive agents, binders and solvents of the same material, stirring and dispersing them, respectively, to prepare a first slurry and a second slurry; controlling the particle size of the active main material in the first slurry to be 20-80% of the particle size of the active main material in the second slurry; the active main material comprises a positive electrode main material or a negative electrode main material; the positive electrode main material comprises any one of lithium cobalt oxide, lithium manganese oxide, lithium nickel oxide, lithium nickel cobalt manganese oxide or lithium nickel cobalt aluminum oxide, or a combination of at least two thereof; the negative electrode main material comprises any one of graphite, hard carbon, soft carbon, silicon, silicon carbon or tin, or a combination of at least two thereof; Taking the total mass of the active main material, the conductive agent and the binder in the first slurry as 100wt%, the content of the binder is 1-3wt%; the content of the binder in the first slurry is controlled to be 30-90% of the content of the binder in the second slurry; the binder includes any one of sodium hydroxymethyl cellulose, styrene-butadiene rubber, polyvinylidene fluoride or polyacrylic acid or a combination of at least two; the conductive agent includes any one of carbon black, carbon fiber, carbon nanotube or graphene or a combination of at least two; (2) coating the first slurry in step (1) on the current collector to form first slurry stripes with gaps; the gaps are 0.5 to 50 mm, the width of the first slurry stripes is 5 to 20 times the gaps; the thickness of the first slurry stripes is 200 to 450 μm; (3) coating the second slurry obtained in step (1) in the gap obtained in step (2) to form second slurry stripes having the same thickness as the first slurry stripes; (4) Baking and rolling are performed in sequence to make the first slurry stripes form first active stripes and the second slurry stripes form second active stripes, which are arranged alternately in sequence to form an active layer; the thickness of the first active stripes is equal to that of the second active stripes, both of which are 150 to 350 μm, and the porosity of the first active stripes is controlled to be 20 to 50%, and the porosity of the second active stripes is higher than that of the first active stripes, so as to obtain a thick electrode.
15. An application of the thick electrode according to any one of claims 1 to 9 or the thick electrode obtained by the manufacturing method according to any one of claims 10 to 14, characterized in that: The applications include using the thick electrodes in lithium-ion batteries.
Citation Information
Patent Citations
Pore-forming method for diaphragms of lithium ion batteries
CN102655229B
Secondary battery
JP2013246900A
Negative electrode for nonaqueous electrolyte secondary batteries, and nonaqueous electrolyte secondary battery
WO2022181489A1